National trachoma surveillance annual report, 2012 - Cowling, C.; Liu, B.; Snelling, Thomas; Ward, J.; Kaldor, J.; Wilson, D. (2015)
This work is copyright. You may download, display, print and reproduce the whole or part of this work in unaltered form for your own personal use or, if you are part of an organisation, for internal use within your organisation, but only if you or your organisation do not use the reproduction for any commercial purpose and retain this copyright notice and all disclaimer notices as part of that Australia remains the only developed country to have endemic levels of trachoma (a prevalence of 5% or greater among children) in some regions. Endemic trachoma in Australia is found predominantly in remote and very remote Aboriginal communities. The Australian Government funds a National Trachoma Surveillance and Reporting Unit to collate, analyse and report trachoma prevalence data and document trachoma control strategies in Australia through an annual surveillance report. This report presents data collected in 2012. Data are collected from Aboriginal and Torres Strait communities designated as at-risk for endemic trachoma in the Northern Territory, Queensland, South Australia and Western Australia. The World Health Organization grading criteria were used to diagnose cases of trachoma in Aboriginal children with jurisdictions focusing screening activities on the 5-9 years age group; however, some children in the 1-4 and 10-14 years age groups were also screened. The prevalence of trachoma within a community was used to guide treatment strategies as a public health response. Aboriginal adults aged 40 years or older were screened for trichiasis. Community screening coverage of the designated at-risk communities was 96%. Screening coverage of the estimated population of children aged 5-9 years and adults aged 40 years or older in at-risk communities was 71% and 31%, respectively. Trachoma prevalence among children aged 5-9 years who were screened was 4%. Of communities screened, 63% were found to have no cases of active trachoma and 25% were found to have endemic levels of trachoma. Treatment was required in 87 at-risk communities screened. Treatment coverage of active cases and their contacts varied from 79%-97% between jurisdictions. Trichiasis prevalence was 2% within the screened communities.